2022
DOI: 10.1111/1475-6773.13916
|View full text |Cite
|
Sign up to set email alerts
|

Simulating the role of knowledge brokers in policy making in state agencies: An agent‐based model

Abstract: Objective To model children's mental health policy making dynamics and simulate the impacts of knowledge broker interventions. Data sources Primary data from surveys (n = 221) and interviews (n = 64) conducted in 2019–2021 with mental health agency (MHA) officials in state agencies. Study design A prototype agent‐based model (ABM) was developed using the PARTE (Properties, Actions, Rules, Time, Environment) framework and informed through primary data collection. In each simulation, a policy is randomly generat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 100 publications
0
7
0
Order By: Relevance
“…Another aspect is problem solver, which includes the ability to notice, understand, and analyze problems before using their capabilities to develop the solution. This characteristic is supported by the concept of the role of KB and is included as an entrepreneurial characteristics [12,34], and it accelerates the decision on the policymaking process [28,35]. The last component of characteristics is convincing stakeholders, which is in line with the model of the approach used by a KB to transfer the ideas or knowledge to specific targets, as proven in previous studies [36][37][38].…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Another aspect is problem solver, which includes the ability to notice, understand, and analyze problems before using their capabilities to develop the solution. This characteristic is supported by the concept of the role of KB and is included as an entrepreneurial characteristics [12,34], and it accelerates the decision on the policymaking process [28,35]. The last component of characteristics is convincing stakeholders, which is in line with the model of the approach used by a KB to transfer the ideas or knowledge to specific targets, as proven in previous studies [36][37][38].…”
Section: Discussionmentioning
confidence: 66%
“…In this study, the idealism for improvement reflects vision and selfencouragement. Moreover, theoretically, idealism implies reality, which is mind-dependent and is influenced by our ideas [28]. For the capacity-building skills, we found that the characteristic comprises several values of a KB, namely, networking skills, communication or persuasion skills, good track record, talent, broadened insight, and knowledge in their field.…”
Section: Discussionmentioning
confidence: 86%
“…Purtle and Colleagues 11 in this issue apply emerging systems science, implementation, and policy analysis methods to inform uptake of programs and policies at the population level. Zivin et al 12 in this issue present novel policy research focused on the health care workforce, especially when faced with potential provider burnout and labor shortages.…”
Section: Cutting‐edge Research Informing Evidence‐based Policy Makingmentioning
confidence: 99%
“…[2][3][4][5] Discrete event simulation (DES), agent-based simulation, system dynamics and hybrid models based on these are common simulation approaches in various domains. [6][7][8][9][10][11][12][13][14][15][16] In the healthcare domain, DES is among the most commonly used method of simulation, 4,11,[17][18][19][20][21][22] where a system is modelled with a number of resources (with defined capacities), queues, and a series of events. 23 The DES approach offers better representations than other afore-mentioned individual techniques to model complex systems involving individual movements between resources and queues.…”
Section: Introductionmentioning
confidence: 99%
“…Discrete event simulation (DES), agent‐based simulation, system dynamics and hybrid models based on these are common simulation approaches in various domains 6–16 . In the healthcare domain, DES is among the most commonly used method of simulation, 4,11,17–22 where a system is modelled with a number of resources (with defined capacities), queues, and a series of events 23 .…”
Section: Introductionmentioning
confidence: 99%